(untitled) - Rodríguez, Patty; Stein, Ariana; Reyes, Citlali ([Los Angeles], 2020)
Walter was a Puerto Rican astrologer, actor, dancer, and writer, best known as a television personality for his shows on daily astrology.
Keywords: Mercado, Walter; Juvenile literature; Astrologers; Juvenile literature; Board books; Bilingual; Spanish language materials; Biography; Biography; Puerto Rico; Television personalities; Juvenile literature; Biography; Puerto Rico; Astrologers; Juvenile literature; Puerto Rico; Biography; Biographies; Biographies; Juvenile works